2006
DOI: 10.1021/ac051993s
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Approach to Quantitation of Reactive Oxygen Species in Mainstream Cigarette Smoke

Abstract: A novel approach to monitoring of mainstream smoke reactive oxygen species (ROS) has been developed and applied to the quantitation of smoke oxidants. Redox-active fluorescent probe dihydrorhodamine 6G (DHR-6G) was selected as the molecular probe because it is sensitive to typical smoke ROS. The experimental system couples an automatic cigarette smoke machine fiber-optic fluorometer for real-time monitoring of the reaction progress between cigarette smoke and DHR-6G. Quantitation was achieved based on the amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Since there was no mainstream smoke, the sample they collected cannot be simply defined as sidestream smoke since puffing a cigarette could affect both the amount and nature of the smoke produced. Ou and Huang (2006) detected a concentration of 391 nmol of ROS/cigarette in mainstream using 2R4F research cigarette (Flicker and Green 2001). They also report burley tobacco cigarette has 10 times higher ROS content than bright tobacco cigarette.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Since there was no mainstream smoke, the sample they collected cannot be simply defined as sidestream smoke since puffing a cigarette could affect both the amount and nature of the smoke produced. Ou and Huang (2006) detected a concentration of 391 nmol of ROS/cigarette in mainstream using 2R4F research cigarette (Flicker and Green 2001). They also report burley tobacco cigarette has 10 times higher ROS content than bright tobacco cigarette.…”
Section: Discussionmentioning
confidence: 95%
“…Kang et al (2002) reported 0.104 ± 0.068 ppbv of gas-phase hydrogen peroxide in the summer in downtown Seoul, Korea. In the past research, people have studied various combustion sources, e.g., vehicles (Hung and Wang 2001), incense burning (Kao and Wang 2002), and cigarettes (Huang et al 2005;Ou and Huang 2006). Both gas phase and PM (mainly tar) are generated in cigarette smoke and both contain radical species (Pryor 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoking was carried out according to ISO 3308 machine smoking standard conditions (35 ml puff, drawn for 2 seconds at 60-second intervals). Quantification of ROS in cigarette smoke was adapted from the reported method with some modification (Ou and Huang 2006). Briefly, five replicates (two cigarettes per replicate) of cigarettes were smoked through a SM-450 smoking machine under ISO regime without using Cambridge filter.…”
Section: Smoke Collection and Determination Of Ros Scavenging Capacitymentioning
confidence: 99%
“…More recently, several fluorescence probes, such as 2, 7-dichlorofluorescein (DCFH), dihydrorhodamine 123, and dihydrorhodamine 6 G (DHR 6 G) have been applied for the detection of ROS in cigarette smoke (Huang, Lin, and Ma 2005;Ou and Huang 2006;Zhao and Hopke 2012). These compounds are nonfluorescent but when oxidized by typical ROS (e.g., O ÀÁ 2 , HO·, R·, RO·, and ROO·), or H 2 O 2 in the presence of horseradish peroxidase they become highly fluorescent dyes that can be quantitatively determined by a fluorescence spectrophotometer.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are various existing methods to assess oxidative damage caused by ROS, such as measuring lipid peroxidation products and DNA adducts, none of them evaluates ROS directly [3][4][5]. After Ou and Huang first demonstrated the use of DHR6G as a fluorometric assay for ROS in cigarette smoke, it logically followed that the use of the same probe to measure the ROS in biological samples should be investigated [6]. The theory behind using DHR6G is that nonfluorescent DHR6G will emit fluorescence after being oxidized by ROS.…”
Section: Introductionmentioning
confidence: 99%